CARD4/NOD1 is not involved in inflammatory bowel disease. Issue 1 (1st January 2003) - Zouali, H; Lesage, S; Merlin, F; Cézard, J-P; Colombel, J-F; Belaiche, J; Almer, S; Tysk, C; O'Morain, C; Gassull, M; Christensen, S; Finkel, Y; et al.
Abstract : Background and aims: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are complex genetic disorders. CARD15/NOD2, a member of the Ced4 superfamily which includes Apaf-1 and CARD4/NOD1, has recently been associated with genetic predisposition to CD but additional genetic factors remain to be identified. Because CARD4/NOD1 shares many structural and functional similarities with CARD15, we tested its putative role in IBD. Patients and methods: The 11 exons of CARD4 were screened for the presence of variants in 63 unrelated IBD patients. The only non-private genetic variation encoding for a substitution in the peptidic chain was genotyped in 381 IBD families (235 CD, 58 UC, 81 mixed, and seven indeterminate colitis families) using a polymerase chain reaction-restriction fragment length polymorphism procedure. Genotyping data were analysed by the transmission disequilibrium test. Results: Five of nine sequence variations identified in the coding sequence of the gene encoded for non-conservative changes (E266K, D372N, R705Q, T787M, and T787K). Four were present in only one family. The remaining variant (E266K), which exhibited an allele frequency of 0.28, was not associated with CD, UC, or IBD. Furthermore, IBD patients carrying sequence variations in their CARD4 gene had a similar phenotype to those with a normal sequence. Conclusion: Our results suggest that CARD4 does not play a major role in genetic susceptibility to IBD.